The Potential of Probiotics in Reducing Ventilator-Associated Pneumonia: A Literature-Based Analysis - Chen, Tao-An; Chuang, Ya-Ting; Pai, Szu-Chi; Zheng, Jin-Fu (Microorganisms (Basel), 2025)
Ventilator-associated pneumonia (VAP) remains a significant concern in intensive care units (ICUs), contributing to increased morbidity, mortality, and healthcare costs. Probiotics and synbiotics have been explored as potential preventive measures due to their ability to modulate gut microbiota, reduce pathogenic colonization, enhance immune responses, and maintain intestinal barrier integrity. While some randomized controlled trials (RCTs) suggest that specific strains, such as Lactobacillus rhamnosus GG and Bifidobacterium breve, may reduce VAP incidence, larger trials have not confirmed significant benefits. Systematic reviews and meta-analyses indicate a potential 28–38% relative risk reduction in VAP, but evidence quality remains low due to methodological limitations and study heterogeneity. Economic evaluations also question the cost effectiveness of probiotic use in ICU settings. Future research should focus on large-scale, multicenter RCTs to determine the optimal strains, dosages, and administration methods, along with standardized diagnostic criteria. Until stronger evidence emerges, probiotics should be considered an adjunctive rather than a primary VAP prevention strategy.